A imagem como documento: a história dos africanos e afro-brasileiros por meio das imagens nos livros didáticos - Sirqueira, Karoline Lima (2022)
This dissertation seeks to understand how images related to African and Afro-Brazilian themes have been addressed in textbooks before and after the implementation of Law 10.639/03, which instituted as mandatory the teaching of African and Afro-Brazilian history and culture within the teaching of history. In order to grasp a fuller understanding, it was initially necessary to address the importance of images in the social imaginary as loaded representations and its relationship with the construction of stereotypes – by doing this, we started from a conception of the image as a broad phenomenon, which goes beyond the limits of the textbook. Then, a survey, analysis and description of images of African and Afro-Brazilian themes were carried out in six books; three of them before the Law and three after Law 10.639/03. This comparative tableau aimed at mapping the way through which images were usually selected to address African and Afro-Brazilian themes (for example, if they were repeated before and after the Law, if there was a preference in relation to some type of image etc). After the analysis and description of the images, a cross-referencing of the data obtained among the analyzed books was carried out to verify recurrences and patterns -- mostly the frequency of representations used in the textbooks that were produced by Europeans from the colonial period (ethnocentrism), and correlation between written information and images (context). Through these different axis, we sought beyond the formal aspects of the visual phenomena in order to understand how each book discussed the images in light of the established contents. Finally, as a product, a didactic proposal was implemented, that aimed at presenting a method of analysis for images based on the method proposed by Panofsky for the interpretation of works of art. Four activities with works of art by contemporary black artists were set out to model further activities, with the same proposal through the lenses of a decolonial perspective. Thus, through this didactic proposal, we intended to contribute to the expansion of methodological possibilities in the use of images within the context of teaching history with African and Afro-Brazilian themes.